The Mechanic Eye: North American Visual Poetry in the Digital Age - Maria Goicoechea de Jorge (Texto Digital)
This paper offers a revision of North American visual poetry from the contemporary perspective of the digital revolution. From the Native American chants to the digital poetry found on the Web, it will explore the internal drives of this sort of poetic manifestations that have endured through different time periods, aesthetic currents and cultural functions despite the various mediums employed for their production and dissemination. Digital poetry nourishes itself from previous literary traditions as well as from the multimedia convergence favored by the digital medium. We will analyze these influences, and the new reading strategies required to contextualize and make sense out of the digital work of poetry. As readers and writers reorganize their reading pacts, researchers of literature face a new challenge: the polymorphic and metamorphosing liquid text made possible by the digital language